A review of swine Influenza: an emerging pandemic (2009)
An unprecedented epizootic swine Influenza A (HINT) virus that is highly pathogenic has crossed the species barrier in Mexico to cause many human fatalities and poses an increasing pandemic threat. This summary describes the aetiopathogenesis of human infection with Influenza A (HINI) and reviews recommendations for prevention and clinical management.